How to do everything with photoshop elements 4.0 - Plotkin, David (McGraw-Hill, 2006)
Edit, organize, and show off your photos using Photoshop Elements 4.0 and the expert tips in this full-color guide. You’ll learn to customize the program to suit your preferences, and then get started retouching, repairing, and enhancing digital images in no time. Step-by-step examples show you how to crop images, fix color, focus, and exposure problems, eliminate defects, manipulate images, add special effects, and much more. You’ll also get tips for getting high-quality prints and creating a Web gallery.